Effects of Habitat and Human Activities on Species Richness and Assemblages of Staphylinidae (Coleoptera) in the Baltic Sea Coast - Ulrich Irmler (Psyche: A Journal of Entomology)
In 2009, the staphylind fauna was studied in six habitats of the Baltic Sea coast of Schleswig-Holstein (northern Germany). The following habitats lagoon, sandy beach, shingle beach, primary dune, wooded cliff, and woodless cliff were significantly separated by their species composition. Vegetation and soil moisture were the most important factors separating the assemblages. Lagoons exhibited the most species-rich habitat. Sandy beaches provided the highest number of endangered species. Both sandy beaches and woodless cliffs showed the highest number of exclusive species. A loss of species was determined in the gradient from sandy to shingle beaches. Few species preferred shingle beaches; abundance of Cafius xantholoma increased with the increasing amount of shingle. More species preferred the sandy conditions, for example, Polystomota grisea, P. punctatella, and Phytosus spinifer. Anotylus insecatus and Bledius defensus require distinct mixtures of sand and silt on woodless cliffs. Tourist impact on sandy beaches accounts for approximately 50% loss of species.